2022
DOI: 10.3390/cancers14030635
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy of Patients with Early Breast Cancer Is Associated with Increased Detection of Disseminated Tumor Cells in the Bone Marrow

Abstract: Preclinical data suggest that neoadjuvant chemotherapy (NAT) may promote micrometastatic spread. We aimed to compare the detection rate and prognostic relevance of disseminated tumor cells (DTCs) from the bone marrow (BM) of patients with early-stage breast cancer (EBC) after NAT with that of therapy-naive EBC patients. DTCs were identified from BM samples, collected during primary surgery. Patients who received NAT were compared to patients who received chemotherapy after surgery. In total, 809 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Moreover, it has been reported that chemotherapy not only increases MenaINV expression but also increases the density of TMEM doorways [19,55] and potentially increases tumor cell dissemination via the blood circulation. Indeed, a recent study indicates that neoadjuvant chemotherapy in patients with early breast cancer leads to an increase in disseminated tumor cells in the bone marrow and subsequent worse overall survival [56]. Therefore, the dismal five-year survival rate for breast cancer patients with metastatic disease of approximately 26% may be due to chemotherapyinduced cancer cell dissemination and increased cancer burden [54,55,[57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that chemotherapy not only increases MenaINV expression but also increases the density of TMEM doorways [19,55] and potentially increases tumor cell dissemination via the blood circulation. Indeed, a recent study indicates that neoadjuvant chemotherapy in patients with early breast cancer leads to an increase in disseminated tumor cells in the bone marrow and subsequent worse overall survival [56]. Therefore, the dismal five-year survival rate for breast cancer patients with metastatic disease of approximately 26% may be due to chemotherapyinduced cancer cell dissemination and increased cancer burden [54,55,[57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that chemotherapy not only increases MenaINV expression but also increases the density of TMEM doorways (19,55) and potentially increases tumor cell dissemination via the blood circulation. Indeed, a recent study indicates that neoadjuvant chemotherapy in patients with early breast cancer leads to an increase of disseminated tumor cells in the bone marrow and subsequent worse overall survival (56). Therefore, the dismal five-year survival rate for breast cancer patients with metastatic disease of approximately 26% may be due to chemotherapyinduced cancer cell dissemination and increased cancer burden (54,55,(57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…Disseminated tumor cells (DTCs) represent one manifestation of MRD: these cells can be detected in the bone marrow (BM) of 20–30% of patients with early breast cancer (EBC) [ 8 ]. Indeed, the detection of DTCs is associated both with a worse outcome and with locoregional and distant recurrence alike [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%